(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, it is revealed that pedagogical skill is a tool that combines the inner essence and external appearance of the teacher’s activity. It allows to understand the totality of methods and means of communicating with the reader through the article.